2021
DOI: 10.3390/ijerph18094956
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Heavy Metal Exposures and Idiopathic Dilated Cardiomyopathy: A Case-Control Study from the Katanga Mining Area of the Democratic Republic of Congo

Abstract: Blood and/or urine levels of 27 heavy metals were determined by ICPMS in 41 patients with dilated cardiomyopathy (DCM) and 29 presumably healthy subjects from the Katanga Copperbelt (KC), in the Democratic Republic of Congo (DRC). After adjusting for age, gender, education level, and renal function, DCM probability was almost maximal for blood concentrations above 0.75 and 150 µg/dL for arsenic and copper, respectively. Urinary concentrations above 1 for chromium, 20 for copper, 600 for zinc, 30 for selenium, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Accidental intoxication among farm workers exposed to CuSO 4 has been reported, and toxic levels of this pesticide can lead to methemoglobinemia and death [ 48 ]. Cardiotoxicity due to exposure to Cu has been reported in zebrafish [ 5 , 16 ], and increased incidence of HF in human was associated with high Cu levels [ 17 , 18 , 19 ]. Owing to its ability to generate ROS, cardiotoxicity of Cu could be directly attributed to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accidental intoxication among farm workers exposed to CuSO 4 has been reported, and toxic levels of this pesticide can lead to methemoglobinemia and death [ 48 ]. Cardiotoxicity due to exposure to Cu has been reported in zebrafish [ 5 , 16 ], and increased incidence of HF in human was associated with high Cu levels [ 17 , 18 , 19 ]. Owing to its ability to generate ROS, cardiotoxicity of Cu could be directly attributed to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Cu caused cardiotoxicity manifested by cellular stress, necrosis, and absence of heartbeat in zebrafish [ 5 , 16 ]. Studies have demonstrated an association between the exposure to high Cu concentrations and the increase in cardiovascular risk and heart failure incidence in humans [ 17 , 18 , 19 ]. Although the mechanisms underlying Cu toxicity are not fully understood, excess reactive oxygen species (ROS), oxidative stress [ 20 , 21 ], and endocrine perturbation [ 22 ] have been implicated.…”
Section: Introductionmentioning
confidence: 99%
“…In another study from Peru, 18 to 35-year-old non-miners living near a mining community, 4400 m above sea level showed a mean BLL of 47.5 µg/L, while unexposed persons in Lima had a mean BLL of 20.3 µg/L [36]. Furthermore, a mean BLL of 56.5 µg/L was reported for a group of people living near a mining area of Katanga in the Democratic Republic of Congo [37]. Overall, 106 or 116 µg/L, respectively, were reported from a study performed in Zambia on adult mothers and fathers of a mining town [14].…”
Section: Adults Living In the Vicinity Of Mining Sitesmentioning
confidence: 91%
“…Miura et al demonstrated that the lower education levels and cold or hot workplaces exhibited a significant association with the development of DCM ( 39 ). Some heavy metals were associated with DCM probability ( 40 ). Although there are still few reports on the relationship between environmental factors and DCM, it is one of the routes of disease disparity, such as the sanitary environment, and further research is required in the future.…”
Section: Dilated Cardiomyopathymentioning
confidence: 99%